β-carotene and other carotenoids as antioxidants - Paiva, Sergio Alberto Rupp de [UNESP]; Russell, Robert M.; Dutta, Sudhir K. (My University, 1999)
Carotenoids are natural pigments which are synthesized by plants and are responsible for the bright colors of various fruits and vegetables. There are several dozen carotenoids in the foods that we eat, and most of these carotenoids have antioxidant activity. β-carotene has been best studied since, in most countries it is the most common carotenoid in fruits and vegetables. However, in the U.S., lycopene from tomatoes now is consumed in approximately the same amount as β-carotene. Antioxidants (including carotenoids) have been studied for their ability to prevent chronic disease. β-carotene and others carotenoids have antioxidant properties in vitro and in animal models. Mixtures of carotenoids or associations with others antioxidants (e.g. vitamin E) can increase their activity against free radicals. The use of animals models for studying carotenoids is limited since most of the animals do not absorb or metabolize carotenoids similarly to humans. Epidemiologic studies have shown an inverse relationship between presence of various cancers and dietary carotenoids or blood carotenoid levels. However, three out of four intervention trials using high dose β- carotene supplements did not show protective effects against cancer or cardiovascular disease. Rather, the high risk population (smokers and asbestos workers) in these intervention trials showed an increase in cancer and angina cases. It appears that carotenoids (including β-carotene) can promote health when taken at dietary levels, but may have adverse effects when taken in high dose by subjects who smoke or who have been exposed to asbestos. It will be the task of ongoing and future studies to define the populations that can benefit from carotenoids and to define the proper doses, lengths of treatment, and whether mixtures, rather than single carotenoids (e.g. β-carotene) are more advantageous.
Keywords: β-carotene; Antioxidants; Carotenoids; Oxidative stress; Retinol; antioxidant; asbestos; beta carotene; carotenoid; antioxidant activity; bioavailability; cancer prevention; carcinogenesis; cardiovascular disease; diet supplementation; drug induced disease; food composition; health promotion; human; review; vegetable; vitamin blood level; vitamin metabolism; vitamin supplementation; Animals; beta Carotene; Biological Availability; Clinical Trials; Fruit; Heart Diseases; Humans; Neoplasms; Vegetables; Angina; Animalia; Lycopersicon esculentum